TINDAK TUTUR DIREKTIF GURU BAHASA INDONESIA DAN RESPON SISWA DALAM PROSES BELAJAR MENGAJAR DI KELAS IX SMP NEGERI 3 BATUSANGKAR - Fitri, Yulia; Basri, Irfani; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTThe purpose of this research is to describe the form of speech act directive, storytelling strategy, context of speech, and student's response to speech act of Indonesian teacher directive in PBM in class IX SMP Negeri 3 Batusangkar. The subjects in this study are Indonesian. Teachers SMP Negeri 3 Batusangkar, Ms. Mis Elli and students of class IX SMP Negeri 3 Batusangkar. Instrument in this research is self-researcher and assisted by recording device (handphone withbrand OPPO A37f), stationery, and observation sheet. The data that have been collected is analyzed by grouping the data of act form of directive speech, story strategy, context of speech, and student response in teaching and learning process. Based on the result of the research, it is concluded four things. First, the most dominant form of speech acts found is the act of speech, but the least directive speech acts are the act of supplication. Second, the dominant narrativestrategy found is a frankly straightforward strategy, while a straightforward strategy of negative politeness is rare, let alone spoken to the heart. Third, the context of the use of strategy in the speech of teacher directive directive to students in the PBM in class IX SMP Negeri 3 Batusangkar using kin greetings, such as "self-nickname" and sometimes "kid" because speech acts directive in PBM teachers used to the opponent more small from the speaker. Fourth, the dominant response found is a positive verbal response, whereas the least-found response is a negative nonverbal response.Kata kunci: tindak tutur direktif, guru, respon siswa